Les anges parlent-ils occitan ? Analyse d’un corpus de noëls toulousains de la seconde moitié du xviiie siècle - Gilles Couffignal (Humanités Numériques)
The collections of noëls printed under the Ancien Régime are an important source for the sociolinguistic history of southern France, given the co-presence of French and Occitan. Critics have focused on the phenomenon of bilingual noëls, in which one or more shepherds speak in Occitan while an angel responds in French. In this paper, we present datasets and analyses enabling us to visualise the role of languages in a corpus of Toulouse noëls from the second half of the eighteenth century. The digital approach, consisting in the automated acquisition of textual sources and the exploitation of analytical databases, thus makes it possible to better address the question of the relationship between languages. In particular, it appears that the micro-genre of bilingual noëls has been overestimated. At the same time, the systematic analysis of the tunes associated with each piece gives us a new insight into the conditions under which these noëls were created.